2023
DOI: 10.1002/adfm.202215034
|View full text |Cite
|
Sign up to set email alerts
|

Flexible Transient Bioelectronic System Enables Multifunctional Active‐Controlled Drug Delivery

Abstract: On-demand drug delivery systems (DDSs) have tremendous promise for clinical in vivo personalized drug delivery. However, the current DDSs are monofunctional and unable to meet the individualized needs of patients. Herein, a biodegradable multifunctional active-controlled drug delivery system (ADDS) is reported. The device can be implanted in various tissues with valves controlled by the deactivation of magnesium (Mg) for rapid drug release from drug reservoirs and long-term drug delivery with the biodegradatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 62 publications
(11 reference statements)
0
6
0
Order By: Relevance
“…The materials used in various previously reported gate valve-type drug delivery bioelectronics were general metal materials (Mg, Mo, etc.). 12,13 Compared to existing materials that have been manufactured through a vacuum process, MXene materials can be easily manufactured through a solution process and have the advantage of minimizing drug loss due to the vacuum process. MXene also features quite excellent conductivity like metallic materials, but it was necessary to check whether degradation due to oxidation and reduction occurs under electrochemical conditions like metallic materials in this system.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The materials used in various previously reported gate valve-type drug delivery bioelectronics were general metal materials (Mg, Mo, etc.). 12,13 Compared to existing materials that have been manufactured through a vacuum process, MXene materials can be easily manufactured through a solution process and have the advantage of minimizing drug loss due to the vacuum process. MXene also features quite excellent conductivity like metallic materials, but it was necessary to check whether degradation due to oxidation and reduction occurs under electrochemical conditions like metallic materials in this system.…”
Section: Resultsmentioning
confidence: 99%
“…Biocompatible metallic materials that undergo crevice reactions in biofluids upon a voltage trigger can serve as actively controlled gates for electrically controlled drug-delivery systems, enabling customizable, programmable control over the timing of release events. 12,13 MXene is a term for layered transition metal compounds of intrinsic metallicity. 14 MXenes constitute a large family of compounds and can be represented as M n +1 X n T x ( n = 1–3), where “M” is an early transition metal, “X” is carbon or nitrogen, and “T” stands for the hydrophilic surface terminations (–O–, –F, and –OH).…”
Section: Introductionmentioning
confidence: 99%
“…To date, most drug delivery devices are nonbiodegradable and designed with a destructive drug release mechanism, which makes them incapable of releasing drugs multiple times or maintaining controlled dosage over time, while necessitating secondary surgery for device extraction after implantable uses ( 73 , 74 ). Recently, some novel electrically controlled DDSs made of biodegradable materials have been developed ( 75 , 76 ), addressing drug leakage concerns during implantation and enabling pulsed drug release. Despite this, achieving precise drug release control (including time and rate) remains a great challenge.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, a suitably designed artificial simulated device can produce an effect comparable to animal experiments while avoiding harm to animals. [ 44 ] The stent test setup is depicted in Figure S5 (Supporting Information) and was tested under axial tension and radial compression ( Figure a). The radial pressure test results (Figure 5b,c) showed that the pressures required to compress 50% of the stent diameter were 3.31±0.09 N (W0), 41.61±4.48 N (W1), 64.78±5.23 N (W2), 74.91±2.21 N (W4) and 27.48±5.98 N (W8).…”
Section: Resultsmentioning
confidence: 99%